2004
DOI: 10.1111/j.1440-1681.2004.04121.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Effects of a Monounsaturated (Palmitoleic) Fatty Acid‐rich Diet Based on Macadamia Nuts in Healthy, Young Japanese Women

Abstract: 1. Recent studies have identified potential beneficial effects of eating nuts, most of which have substantial amounts of monounsaturated fatty acids (MUFA). Macadamia nuts consist of 75% fat by weight, 80% of which is MUFA (palmitoleic acid). 2. To examine variations in serum lipid levels in response to a high-MUFA diet based on macadamia nuts, 3 week interventions of macadamia nuts, coconuts and butter were determined in young, healthy Japanese female students. 3. After 3 weeks intervention, serum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 6 publications
(4 reference statements)
0
38
1
4
Order By: Relevance
“…Nevertheless, neither alanine nor arginine supplementation modified plasma or adipose tissue palmitoleic acid in rats (41). Natural sources of cis-palmitoleate as fish and macadamia oil could increase the blood concentration of this isoform (42,43). For instance, a 1.3-fold increase in circulating palmitoleate was achieved in hypercholesterolemic men after they consumed macadamia nuts (43).…”
Section: Dietary Palmitoleatementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, neither alanine nor arginine supplementation modified plasma or adipose tissue palmitoleic acid in rats (41). Natural sources of cis-palmitoleate as fish and macadamia oil could increase the blood concentration of this isoform (42,43). For instance, a 1.3-fold increase in circulating palmitoleate was achieved in hypercholesterolemic men after they consumed macadamia nuts (43).…”
Section: Dietary Palmitoleatementioning
confidence: 99%
“…Also, the consumption of trans-palmitoleate from dairy was associated with lower amounts of inflammation, but mixed relations with serum lipids (19,33). In various studies (42,43,92), but not all studies (93), the consumption of macadamia nuts (which contain high cis-palmitoleate concentrations) was related to favorable serum lipid profiles.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…A recent study in humans has indicated that body weight and body mass index decreased in a group fed macadamia nuts, which contain large amounts of C16 : 1. 20) In addition, synthesized C16 : 1 in adipose tissue leads to suppress lipogenesis and increase β-oxidation in the liver. 21) Therefore, a diet containing C16 : 1 or synthesized C16 : 1 may potentially lead to decrease in body weight and WAT weight depending on the increase in lipolysis and β-oxidation in the liver and WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Ácidos graxos são importantes moléculas sinalizadoras celular, capazes de modular o metabolismo das células e tecidos por mecanismos distintos, que favorecem ou previnem o desenvolvimento de doenças como o diabetes tipo II, aterosclerose e obesidade (10)(11)(12)(13). Em sua estrutura, o tamanho da cadeia carbônica e o número/posição das duplas ligações determinam suas propriedades físicas e químicas, conferindo a cada um deles funções biológicas únicas (14).…”
Section: Introductionunclassified
“…Accordingly, palmitoleic acid was demonstrated to enhance whole body glucose disposal and to attenuate hepatic steatosis in high-fat-fed mice (3,45) and to protect pancreatic ␤-cells from death induced by palmitic acid (4,25). Furthermore, intake of a diet enriched in palmitoleic acid was associated with improvement of circulating lipid profile in both rodents (24) and humans (10,13). Despite of all these important metabolic effects in liver, skeletal muscle, and ␤-cells, whether palmitoleic acid also affects adipose tissue TAG metabolism remains to be investigated.…”
mentioning
confidence: 99%